Macroeconomic and trade policies and structural adjustment in relation to regional integration in the Caribbean: an overview - Bourne, Compton ([s.n.] [S.l.], 1994)
Attempts to identify and assess the influences of structural adjustment policies on regional integration. Highlights major global economic trends impinging upon approaches to be taken to the CARICOM Single Market and Economy. Focuses on merchandise trade, institutional arrangements governing trade and investment including the ascendancy of transnational arrangements and international finance.